A case of rheumatic fever with multiple recurrences of carditis - Cetin, Ibrahim Ilker; Bikmaz, Yunus Emre; Varan, Birgül; Tokel, Kürşad (The Turkish Journal of Pediatrics, 2008)
Rheumatic fever is still one of the major public health problems in developing countries. Recurrences have been reported during continuous regular prophylaxis. Here, we describe a 13-year-old girl who had four apparent recurrences of carditis while on a regimen of intramuscular benzathine penicillin G (BPG) every three weeks. The interesting and special features of this case were the presence of frequent recurrences of carditis with no evidence of arthritis despite regular BPG injections every three weeks, the requirement of long-term corticosteroid therapy due to these recurrences, and the shortness of time periods between attacks after withdrawal of steroid therapy. In this case, the administration of supraphysiologic doses of glucocorticoids caused iatrogenic Cushing syndrome with decreased bone mineral density and bilateral avascular tibial necrosis mimicking the symptoms of arthritis. Thus, this is a rare case. In similar cases with recurrences of either arthritis or carditis, instead of long-term corticosteroid therapy, we suggest a regimen of BPG prophylaxis every two weeks rather than every three weeks or monthly BPG injections because of the superiority of the every two weeks schedule in the adequate control of rheumatic fever recurrences, as shown in some previous studies.